ARID1A in cancer: Friend or foe? - Fontana, Beatrice; Gallerani, Giulia; Salamon, Irene; Pace, Ilaria; Roncarati, Roberta; Ferracin, Manuela (Frontiers in Oncology, 2023)
ARID1A belongs to a class of chromatin regulatory proteins that function by maintaining accessibility at most promoters and enhancers, thereby regulating gene expression. The high frequency of ARID1A alterations in human cancers has highlighted its significance in tumorigenesis. The precise role of ARID1A in cancer is highly variable since ARID1A alterations can have a tumor suppressive or oncogenic role, depending on the tumor type and context. ARID1A is mutated in about 10% of all tumor types including endometrial, bladder, gastric, liver, biliopancreatic cancer, some ovarian cancer subtypes, and the extremely aggressive cancers of unknown primary. Its loss is generally associated with disease progression more often than onset. In some cancers, ARID1A loss is associated with worse prognostic features, thus supporting a major tumor suppressive role. However, some exceptions have been reported. Thus, the association of ARID1A genetic alterations with patient prognosis is controversial. However, ARID1A loss of function is considered conducive for the use of inhibitory drugs which are based on synthetic lethality mechanisms. In this review we summarize the current knowledge on the role of ARID1A as tumor suppressor or oncogene in different tumor types and discuss the strategies for treating ARID1A mutated cancers.